2018
DOI: 10.1021/acs.jafc.8b01113
|View full text |Cite
|
Sign up to set email alerts
|

Valine Supplementation in a Reduced Protein Diet Regulates Growth Performance Partially through Modulation of Plasma Amino Acids Profile, Metabolic Responses, Endocrine, and Neural Factors in Piglets

Abstract: The objective of this study was to investigate whether valine (Val) supplementation in a reduced protein (RP) diet regulates growth performance associated with the changes in plasma amino acids (AAs) profile, metabolism, endocrine, and neural system in piglets. Piglets or piglets with a catheter in the precaval vein were randomly assigned to two treatments, including two RP diets with standardized ileal digestible (SID) Val:Lysine (Lys) ratio of 0.45 and 0.65, respectively. The results indicated that piglets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…This can be due to reduced FI, increased EE and altered metabolism of BCAA and gut microbiota composition in pigs fed with VLP diets 33 . Although previous research has provided evidence on beneficial effects of supplemental BCAA on growth of nursery and growing pigs fed with diets with normal 31,32 or slightly low protein content 19,22,23,[25][26][27][28][29][30]39 diets, little is understood whether supplementing VLP diets with BCAA can partially or completely recover the VLP induced depression of growth performance. In the current study, supplementing VLP diets with BCAA at levels recommended by Nutrient Requirements of Swine 8 delayed the onset of reduction in BW in nursery pigs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be due to reduced FI, increased EE and altered metabolism of BCAA and gut microbiota composition in pigs fed with VLP diets 33 . Although previous research has provided evidence on beneficial effects of supplemental BCAA on growth of nursery and growing pigs fed with diets with normal 31,32 or slightly low protein content 19,22,23,[25][26][27][28][29][30]39 diets, little is understood whether supplementing VLP diets with BCAA can partially or completely recover the VLP induced depression of growth performance. In the current study, supplementing VLP diets with BCAA at levels recommended by Nutrient Requirements of Swine 8 delayed the onset of reduction in BW in nursery pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of slightly low protein diets (17% crude protein [CP]) with all BCAA improved the growth performance of nursery 22 26 and growing 27 pigs. Dietary deficiency of valine decreased the average daily feed intake (ADFI) and growth performance of weaned pigs 17 and supplementing slightly protein deprived diets with isoleucine and valine protected nursery and growing pigs against reduction in feed intake (FI) and body weight (BW) 7 , 19 , 28 30 . Further, the average daily gain (ADG) was increased with increasing the standard ileal digestibility (SID) valine:lysine in standard protein diets of nursery 31 and growing pigs 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, fermented corn-soybean meal in our study improved daily gain by 40%, and shortened the time to market by 20 d, indicating fermented meal dramatically promoted pig growth. Based on the well-documented effects of Val (Zhang et al, 2018) or Arg (Hu et al, 2017) on pig growth, we speculate that the increased supply of functional amino acids might contribute to the growth-promoting effects of FF.…”
Section: Discussionmentioning
confidence: 90%
“…Another possibility is that the valine to lysine ratio was higher in CD (0.94) than PD (0.85). Study showed that when the valine to lysine ratio was higher, the concentration of leucine and isoleucine was lower at 40 min after feed intake [31]. Because BCAAs share the same enzymes to compete for transamination and oxidative decarboxylation catalysis [30].…”
Section: Discussionmentioning
confidence: 99%